2012
DOI: 10.3130/jaabe.11.71
|View full text |Cite
|
Sign up to set email alerts
|

Design Approach for the Optimal Model of an Energy-Efficient Timber Building with Enlarged Glazing Surface on the South Façade

Abstract: This paper presents the reasonability of using an increased proportion of glazing surfaces in prefabricated timber-frame buildings with a special focus on energy efficiency by using an enlarged glazing area in the south façade. The research is based on a case study of a two-storey house built in a prefabricated timberframe structural system taking the climate data for Ljubljana into consideration. Parametric analysis is performed on the variation of an increased proportion of the glazing surface's impact in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Numerous research papers (Yan et al, 2014;Lee et al, 2012;Leskovar and Premrov, 2012) concerning new methods in this field have appeared in journals and been presented at conferences.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research papers (Yan et al, 2014;Lee et al, 2012;Leskovar and Premrov, 2012) concerning new methods in this field have appeared in journals and been presented at conferences.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, it was found that the use of timber frames in multistorey buildings could reduce embodied carbon by 48% in comparison with steel and by 19% compared to concrete as the principal structural material. Moreover, timber is renewable and lightweight, with good thermal properties and a low carbon footprint (Svatoš-Ražnjević, 2022; Hens et al , 2021; Kunic et al , 2021; Ostrowska-Wawryniuk, 2021; Bukauskas et al , 2019; Stavric and Bogensperger., 2015; Daerga et al , 2014; Leskovar and Premrov, 2012; Weinand, 2009). Additionally, timber provides an agreeable indoor microclimate and has positive effects on the occupants of the building, while reducing stress (Ostrowska-Wawryniuk, 2021; Tarin et al , 2019; Leskovar and Premrov, 2012).…”
Section: Reuse In Timber Designmentioning
confidence: 99%
“…Moreover, timber is renewable and lightweight, with good thermal properties and a low carbon footprint (Svatoš-Ražnjević, 2022; Hens et al , 2021; Kunic et al , 2021; Ostrowska-Wawryniuk, 2021; Bukauskas et al , 2019; Stavric and Bogensperger., 2015; Daerga et al , 2014; Leskovar and Premrov, 2012; Weinand, 2009). Additionally, timber provides an agreeable indoor microclimate and has positive effects on the occupants of the building, while reducing stress (Ostrowska-Wawryniuk, 2021; Tarin et al , 2019; Leskovar and Premrov, 2012). It seems possible that timber, especially for taller buildings, is a viable choice that could potentially decrease the environmental impact of construction.…”
Section: Reuse In Timber Designmentioning
confidence: 99%
“…The importance of thermal transmittance of the wall and its effect on the glazing size in a timber building in Ljubljana, Slovenia was studied by Leskovar et al [15]. Different thermal values for windows were also studied in order to find the optimal area of window on south-facing façades.…”
Section: Introductionmentioning
confidence: 99%